Infectious Airborne Disease Knowledge, Training Preferences, and Peer Support Acceptance among Young Working Autistic Adults: A Qualitative Inquiry. - Pfeiffer, Beth; Davidson, Amber; Kelly, Patrick JA; Luck, Caseem; Singley, Katie; Bass, Sarah (Journal of Vocational Rehabilitation, 2025)
Background: Infectious airborne diseases (IADs) affect an estimated 25–50 million people annually in the US, leading to over 150,000 hospitalizations and billions of dollars in economic costs. Various preventive measures are readily available and implementable to mitigate IADs in workplaces, including mask wearing, social distancing, and handwashing. However, autistic individuals face increased IAD risks due to social communication differences and challenges accessing and following preventive recommendations. Objective: This qualitative study aimed to explore IAD understanding among young working autistic adults, including overall knowledge, preferred training methods, and peer support acceptability. Methods: 20 one-on-one semi-structured interviews were conducted, transcribed, and analyzed using Dedoose with autistic adults. Results: Twenty autistic adults, 70% male, with a mean age of 25.8 participated in the study.40% reported additional mental health conditions, while 60% cited learning disabilities. 50% of participants identified as white, 40% as black or African American, and 10% as other for race. Key domains and subtopics include IAD conceptualization, workplace protection facilitators and barriers, information channels, and perceptions of peer support. From these key domains, four overarching themes surfaced: 1) established germ knowledge, 2) engagement in preventive measures, 3) information gathering and appraisal, and 4) perceptions of peer-to-peer learning. Conclusion: This study calls attention to the lack of tailored training for autistic individuals to mitigate IAD risks in workplaces. Insight into knowledge, preferred training methods, and peer support acceptance informs the development of accessible resources. Understanding these aspects is fundamental in developing effective strategies to enhance IAD prevention among autistic individuals in workplace settings.